Insight on population structure of the Chilean jack mackerel (Trachurus murphyi) - Gerlotto, François; Gutiérrez, Mariano; Bertrand, Arnaud (Aquatic living resources (Montrouge), 2012)
The Chilean jack mackerel (Trachurus murphyi) is one of the most important exploited fish populations in the world. Its area of distribution covers the sub-tropical waters of the South Pacific Ocean, from South America up to New Zealand and even Australia. It is subject to high variations in biomass, with annual world catches varying from less than 0.5 to almost 5 million tonnes. Management of this species and its fishery requires a correct understanding of the population structure. Although several hypotheses have been proposed, suggesting that there are up to four independent populations, genetic analysis indicates only a single population in the South Pacific Ocean. We consider the two most probable structures for this population: a “patchy population”, where all the fish belong to a single population that expands and contracts depending on the biomass; and a metapopulation, where a source population creates several subpopulations that can remain independent during prolonged periods, depending on the environmental conditions. We studied the conditions for these hypotheses to represent reality, especially the demographic structure and existence of different spawning areas. Using knowledge obtained from fisheries and acoustic surveys, we show that if we apply their definitions strictly, neither of the two hypotheses can be fully rejected. Nevertheless, some particular spatial characteristics observed recently between the Peruvian and Centre-South Chilean parts of the distribution lead us to conclude that the metapopulation definition is likely to better describe the stock. The consequences of each population structure for fisheries management are listed, showing that the metapopulation hypothesis represents a safer definition for stock assessment. We conclude that T. murphyi can be described as a metapopulation, but also that the definitions proposed in the literature on metapopulations are not fully adapted to pelagic fish populations with a basin-scale distribution range, and suggests specific research that could be done in this field.